Climate Shocks, Vulnerability, Resilience and Livelihoods in Rural Zambia - Ngoma, Hambulo; Finn, Arden; Kabisa, Mulako (World Bank, Washington, DC, 2021)
To what extent do the behavioral choices of Zambian smallholder farmers influence the negative effects of climate shocks, and what impact do these choices have on vulnerability and resilience? This paper uses nationally representative, three-wave household-level panel data to investigate these questions. The empirical estimation employs an instrumental variable probit regression model, which also controls for the endogeneity of key choice variables. There are four main empirical findings. First, droughts are the most prevalent climate shock rural smallholder farmers in Zambia face, but the extent of exposure differs spatially, with the Southern and Western Provinces being the hardest hit. Nationally, about three-quarters of all smallholder farmers are vulnerable and only about one-quarter are resilient. Second, increased climate shocks correlate with both increased vulnerability and reduced resilience, with short- and long-term deviations in seasonal rainfall worsening vulnerability and resilience. Third, higher asset endowments and education level of the household head reduce vulnerability and increase resilience among smallholder farmers. Female-headed households are more vulnerable and less resilient, on average. Fourth, the use of climate-smart agricultural practices—namely, minimum tillage and use of inorganic fertilizers or hybrid maize seed—significantly improves household resilience in the short term. The paper draws two main policy implications from the findings. First, the results point to an urgent need to invest in research and development for climate shock–tolerant crop varieties and in broader climate-smart agricultural technologies to scale out and scale up context-specific practices through innovative digital platforms. Second, more investment is needed in risk mitigation strategies such as weather indexed insurance, targeted social cash transfers and how to make these work effectively for smallholder farmers. Other important complementary elements include investment in innovative digital platforms that can facilitate timely delivery of climate information services and facilitating asset accumulation and education that can enable farmers to improve climate shock resilience over time.